2016
DOI: 10.3390/foods5030056
|View full text |Cite|
|
Sign up to set email alerts
|

Increase of Chamazulene and α-Bisabolol Contents of the Essential Oil of German Chamomile (Matricaria chamomilla L.) Using Salicylic Acid Treatments under Normal and Heat Stress Conditions

Abstract: The chamazulene and α-(−)-bisabolol contents and quality of the chamomile oil are affected by genetic background and environmental conditions. Salicylic acid (SA), as a signaling molecule, plays a significant role in the plant physiological processes. The aim of this study was to evaluate the chemical profile, quantity, and improve the essential oil quality as a consequence of the increase of chamazulene and α-(−)-bisabol using salicylic acid under normal and heat stress conditions by the gas chromatography-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 24 publications
(43 reference statements)
1
33
0
1
Order By: Relevance
“…(E)-nerolidol, on the other hand, showed positive correlation with temperature, suggesting that it may play some role on alleviation of heat stress on B. dracunculifolia. Similarly, heat stressed chamomile plants were reported to produce higher amounts of nerolidol [62]. Another possibility is the fact that higher temperatures, up to 30 °C, increase herbivory [63], and nerolidol, as a well studied inducible herbivoredefense mechanism [64], may be accumulated in response to such environmental conditions.…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…(E)-nerolidol, on the other hand, showed positive correlation with temperature, suggesting that it may play some role on alleviation of heat stress on B. dracunculifolia. Similarly, heat stressed chamomile plants were reported to produce higher amounts of nerolidol [62]. Another possibility is the fact that higher temperatures, up to 30 °C, increase herbivory [63], and nerolidol, as a well studied inducible herbivoredefense mechanism [64], may be accumulated in response to such environmental conditions.…”
Section: Antioxidant Activitymentioning
confidence: 98%
“…The chemical composition of German chamomile varies from place to place, depending on soil, the specific environment and different genotypic backgrounds over the locations [ 15 ]. Some of the earlier studies on the secondary metabolites of German chamomile reported more than 120 compounds [ 16 , 17 , 18 , 19 , 20 ]. Among these active compounds, terpenoids (28 types) and flavonoids (36 types) are considered to be the important components classes.…”
Section: Chemistry Processing and Ethanopharmacologymentioning
confidence: 99%
“…2) ). The content of different compounds in the plant depends on genetic, ontogenetic and environmental factors (Raal et al, 2012[ 106 ]; Ghasemi et al, 2016[ 43 ]). Dried chamomile flowers contain up to 2 % of essential oils (McKay and Blumberg, 2006[ 88 ]), up to 50 % of phenolic substances (Haghi et al, 2014[ 50 ]), and 10-26 % of minerals among which K, Ca, Mg are present in the highest concentrations (McKay and Blumberg, 2006[ 88 ]).…”
Section: Chemical Composition Of Chamomile Flowersmentioning
confidence: 99%
“…Sequiterpenes include mainly azulenes (1-15 %) with chamazulene being the most abundant, α-bisabolol and its oxides (up to 78 %), and trans-β-farnesene (12-28 %) (Kazemi, 2015[ 60 ]; Stanojevic et al, 2016[ 125 ]). Flowers also contain non-violate proazulenes (sesquiterpene lactones) like matricin (0.03-0.20 %) and matricarin, that can be partially converted during steam distillation into violate chamazulene of blue color (Capuzzo et al, 2014[ 15 ]; European Medicines Agency, 2015[ 29 ]; Ghasemi et al, 2016[ 43 ]). Bisabolol, a monocyclic sequiterpene alcohol, and bisabol oxides A-D are main constituents providing the aroma of essential oils (Sharifi-Rad et al, 2018[ 119 ]).…”
Section: Chemical Composition Of Chamomile Flowersmentioning
confidence: 99%